Desenvolvimento de hidrogel biopolimérico para aplicação em soluções agrícolas - (:unkn) unknown (Universidade Federal do Pampa, 2025)
Climate change represents one of the greatest challenges to agriculture, a sector that is fundamental to food security and human development. Climate instability has continuously affected water availability, soil quality, and crop productivity. In this context, the development of technologies that promote more sustainable and resilient agricultural production becomes essential. Hydrogels emerge as a promising solution due to their ability to retain large amounts of water and gradually release it into the soil, thereby reducing the need for frequent irrigation and helping to maintain soil moisture during drought periods. In addition, these materials allow the incorporation and sustained release of nutrients, optimizing the use of agricultural inputs such as fertilizers or herbicides and contributing to more efficient farming practices. In order to make this technology more accessible and sustainable, the present study aimed to develop biopolymeric hydrogels using different crosslinking methods and green crosslinking agents. These compounds not only replace toxic crosslinkers but also offer advantages such as biodegradability and biocompatibility. The biopolymeric hydrogels were synthesized using the casting method for chemical crosslinking and ionic crosslinking using chloride ions, with fertilizer incorporation during the preparation stage. The analyses included swelling behavior, sustained nutrient release, and in vivo tests with application to lettuce seedlings, allowing the evaluation of hydrogel performance under conditions simulating agricultural use. The synthesized hydrogels exhibited differences according to the type of crosslinking. In swelling tests, the chemically crosslinked formulation reached 1106,10 ± 7,50%, while the ionically crosslinked hydrogel showed 212 ± 9,97%, highlighting the influence of crosslinking density on water absorption capacity. In sustained release tests, both formulations released the fertilizer gradually, although with distinct behaviors: the chemically crosslinked hydrogel showed a slower initial release, whereas the ionic hydrogel exhibited a more uniform release profile. In in vivo assays, the ionic hydrogel promoted better seedling development, while the chemically crosslinked hydrogel showed slight interference with early growth. Overall, the hydrogels demonstrated strong potential for agricultural applications due to their water retention capacity and sustained nutrient release, meeting the demand for more sustainable materials in the agricultural sector.
Keywords: Hidrogel; Reticulação Verde; Agricultura; Condicionante; Liberação sustentada; Hydrogel; Green Crosslinking; Agriculture; Soil Conditioner; Sustained Release; ENGENHARIAS